East Asian American cultural essentialism - Chiou, Andy Y.; Feng, Jing Betty (Frontiers in Organizational Psychology, 2024)
We conduct a two-study sequential mixed-methods exploratory research to explore the culturalpsychological factors driving the individual differences between East Asian Americans who break through the bamboo ceiling and those who do not. In Study 1, based on 19 one-on-one semi-structured interviews, cultural essentialism and bicultural identity integration emerged from the interview data as contributing factors. Interviewees who exhibited essentialist or social constructionist beliefs showed different behavioral and career patterns. Study 2 collected 338 survey respondents to quantitatively test this mediating relationship. The findings from both qualitative and quantitative data suggest that having more fluid concepts of culture, associating with more integrated bicultural identities, may improve career prospects in a multicultural work environment. This paper offers practical implications for Asian Americans who desire to achieve their career goals to be authentic self while remaining adaptable and developing a mindset of "flexibility". While the organizations should emphasize on intercultural interactions and leverage bicultural employees as change agent to support their DEI initiatives.